-6(x+40)=-28-4x

Simple and best practice solution for -6(x+40)=-28-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+40)=-28-4x equation:



-6(x+40)=-28-4x
We move all terms to the left:
-6(x+40)-(-28-4x)=0
We add all the numbers together, and all the variables
-6(x+40)-(-4x-28)=0
We multiply parentheses
-6x-(-4x-28)-240=0
We get rid of parentheses
-6x+4x+28-240=0
We add all the numbers together, and all the variables
-2x-212=0
We move all terms containing x to the left, all other terms to the right
-2x=212
x=212/-2
x=-106

See similar equations:

| 9(c-9)=63 | | 3m-1=10 | | 34-4x=6(7x-2) | | 2u=12-4 | | 34-4x=67x-2 | | 5s+53=s+65 | | 3(x−5)=12.​ | | 5s+53=s+64 | | 6y=2y+40 | | -3+7x=-8(1-x) | | 2x-1+3x+9=18 | | 4(x-3)=-12-6x | | 2s=3s–37 | | 6k=44 | | 10+6w=8w | | 5=6+3y | | 17z+37=5z+97 | | 12-3+4x=45 | | x/2+0.25=0.6 | | X+45+2x-15=180 | | 34=w/3+10 | | 6c–2=4c+10 | | a+66=7a | | y+28=8y | | 6x+7=10x-9 | | -4j+-2=-10 | | -3(x+14)=12 | | 200÷8=x | | x(.15)=5000 | | 2a+3=5a–69 | | 3x=1/2x+30 | | 4u=2u-18 |

Equations solver categories